Fund-Specific Determinants of Performance: An Empirical Study of Islamic and Conventional Mutual Funds of Pakistan - Ahmad, Yaqoob; Sun, Guangguo; Khidmat, Waqas Bin (International Journal of Economics and Financial Issues, 2017)
This study is an attempt to investigate the fund-specific determinants of performance of conventional and Islamic mutual funds in Pakistan. For this purpose, Sharpe Ratio, Sortino Ratio, Information Ratio and Jensen Alpha are used as proxies of funds' performance. We examine several fund-specific characteristics as potential determinants of fund performance such as fund size, turnover, liquidity, management fee, expense ratio, new money, fund age and fund family. A sample of 100 open ended mutual funds were evaluated for a period from 2011-2016. This sample is further divided into overall, conventional and Islamic funds. Data was extracted from the annual reports of mutual funds, business recorder and the daily NAV is obtained from the website of Mutual Fund Association of Pakistan. Fixed and Random effect methodology is used for the data analysis of this study. The result shows that turnover and new money have a significant positive impact on Sharpe ratio for all three samples of funds. Liquidity is positively and significantly related with Sharpe ratio in case of Islamic funds while for conventional funds age has a significant positive effect on fund's performance. Expense ratio is negatively associated with Sharpe ratio in case of conventional funds. The finding suggested that turnover, liquidity and new money demonstrates significant positive relation with information ratio for conventional funds. On the contrary, Islamic funds' performance is worsen by the new money. Sortino ratio is influenced significantly positive by fund family and fund age for all the three sample of funds. Turnover has a positive impact on the Sortino ratio of Islamic funds while management fees has negative influence on the Sortino ratio .Fund family and liquidity has been found to be significantly positively related with Jensen alpha of conventional funds while new money has significant negative effect on the Jensen alpha. Keywords: Mutual Fund, Fund-Specific Determinants, Performance, Pakistan. JEL Classifications: G10, G23